Demystifying Rising Income Inequality Influence on Shadow Economy: Empirical Evidence from Nigeria - Haruna, Emmanuel Umoru; Alhassan, Usman (Review of Economic Analysis, 2022)
We investigate whether rising income disparity contributes to the proliferation of shadow economic activities in Nigeria. The study uses data from 1991 to 2018 and adopts the Auto-regressive Distributed Lags (ARDL) cointegration approach to study the effects of income inequality on the shadow economy in both the short- and the long-run. Our results show that the Nigerian shadow economy responds positively to increases in income inequality, especially in the short run. We also find that the large income disparity in Nigeria drives the poor into informal economic activity, primarily for survival, and that unemployment partly contributes to informality. Our findings suggest that unemployment may be both a result and a cause of rising income disparity in Nigeria, leading to an expansion of the shadow economy. These findings indicate that regulating the proliferation of shadow economic activities in Nigeria will necessitate, among other things, the implementation of measures to reduce income gaps, such as stronger institutional frameworks and the expansion of financial intermediation services such as credit supply to the informal sectors.